Religijne święta w brazylijskim katolicyzmie ludowym (Przegląd Religioznawczy – The Religious Studies Review, 2020)
Since the beginning of colonization, Brazilian Catholicism has been characterized by borrowing elements of religious practices from the many cultures among which it operated. Syncretism has always been an important feature of Brazilian religiousness, especially in its folk dimension, including all kinds of religious festivals - not only those accepted by the Church as official forms of religious life, but also those barely tolerated or totally rejected by the Church’s hierarchy. Referring to the experiences from the field research, the author of the article presents the characteristics of the celebration of some religious holidays in Salvador da Bahia, drawing attention to how the saints of Catholic religious worship function in syncretic local culture (especially in the context of popular Afro-Brazilian cults), how these festivals were initiated, how they evolved and what kind of socio-cultural transformations they are undergoing. In this context the author pays special attention to the processes of “carnivalisation” of the Catholic religious festivities, increasing their significance in the sphere of profanum and obscuring their original religious symbolism.